2006
DOI: 10.1038/sj.ejcn.1602578
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves albumin fractional synthetic rate in chronic hemodialysis patients

Abstract: Objective: To determine whether exercise augments the improvements in fractional synthetic rate (FSR) of albumin observed with nutrition alone. Design: Randomized crossover study. Each patient randomly participated in two protein metabolism kinetic studies using primed-constant infusion of ( 13 C) leucine 2 h before, during and 2 h after hemodialysis. Plasma enrichments of ( 13 C) leucine and ( 13 C) ketoisocaproate were examined to determine the FSR of albumin. IntroductionChronic hemodialysis (CHD) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…Multiple studies demonstrated that resistance exercise combined with oral nutritional supplementation facilitates muscle uptake of amino acids and muscle protein accretion in healthy subjects, which is believed to be due to increased blood flow to the muscle as well as enhanced insulin signaling in the cellular level24-27. In accordance with these data, several short-term studies in CHD patients showed that net muscle protein accretion and albumin synthesis are increased with nutritional supplementation combined with exercise when compared to supplementation alone13, 28, 29. Of note, these beneficial effects of combined intervention were above and beyond of what nutritional supplementation provided alone.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple studies demonstrated that resistance exercise combined with oral nutritional supplementation facilitates muscle uptake of amino acids and muscle protein accretion in healthy subjects, which is believed to be due to increased blood flow to the muscle as well as enhanced insulin signaling in the cellular level24-27. In accordance with these data, several short-term studies in CHD patients showed that net muscle protein accretion and albumin synthesis are increased with nutritional supplementation combined with exercise when compared to supplementation alone13, 28, 29. Of note, these beneficial effects of combined intervention were above and beyond of what nutritional supplementation provided alone.…”
Section: Discussionmentioning
confidence: 90%
“…Further, Pupim et al. 42 have noted that one 15 min bout of intradialytic cycling in combination with intradialytic parenteral nutrition can increase the fractional synthetic rate of albumin, a direct estimate of hepatic albumin synthesis, versus intradialytic parenteral nutrition alone (26.2 ± 3.1%, 17.7 ± 1.9%; P < 0.05). However, it is not clear at present if the increase in serum albumin observed in these trials would be associated with an improvement in muscle CSA, as it was not measured concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have uniformly called for targeted interventions to ameliorate chronic inflammation in dialysis patients 49,51,67 and recent data suggest that intradialytic exercise may be effective in this capacity 20,68,69 …”
Section: Intradialytic Exercise Targets Systemic Inflammationmentioning
confidence: 99%
“…Pupim et al. 69 have noted that a single 15 min bout of intradialytic cycling combined with intradialytic parenteral nutrition increased the fractional synthetic rate of albumin, a direct estimate of hepatic albumin synthesis, versus intradialytic parenteral nutrition alone (26.2% ± 3.1%, 17.7% ± 1.9%; P < 0.05).…”
Section: Intradialytic Exercise Targets Systemic Inflammationmentioning
confidence: 99%